Upaya Meningkatkan Hasil Belajar Siswa Kelas IV pada Mata Pelajaran IPAS Menggunakan Metode Problem Based Learning dengan Bantuan Media Wordwall - Lestari, Mugiarti; Karma, I Nyoman; Pratiwi, Diani (Mataram University, 2025)
This study aims to enhance learning motivation among second-grade students at SDN 14 Cakranegara through the implementation of Wordwall as an instructional medium. The research employed a qualitative descriptive method, integrating both qualitative and quantitative data analyses. The study was designed as a Classroom Action Research (CAR) involving 32 students as participants. The findings showed that during the first cycle, the average learning outcome score using Wordwall media reached 64%, categorized as moderate achievement. In the second cycle, the average score increased to 86%, categorized as very good achievement. These results indicate that the use of Wordwall as an interactive learning medium effectively enhances students’ learning motivation, particularly in mastering question sentence material among second-grade students at SDN 14 Cakranegara.